Another man's moccasins - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2009)
Called to investigate when a dead Vietnamese girl is found along a Wyoming highway, Longmire and his deputies have little to go on. Near the crime scene, however, Longmire discovers Virgil White Buffalo, a homeless Indian and Vietnam vet who happens to have the girl's purse. Longmire retrieves a photograph from the purse--a photo that reminds him of his first investigation as a Marine detective in Vietnam. He's sure that the two crimes--separated by 40 years--are connected, but old enemies lie in wait to thwart his search for answers.